Effect of sudden expansion for varied area ratios at subsonic and sonic flow regimes - Sethuraman, Vigneshvaran; Khan, Sher Afghan (NOVA Science Publishers, 2016)
This study investigates the effect of sudden expansion of air in cylindrical pipes of varied area (AR) and length-to-diameter (L/D) ratios, at subsonic and sonic flow regimes. It was found that the flow reattaches at approximately same location of the pipe, irrespective of the area ratio for the cases 2.56 and 3.61. At minimal area ratio of 1.69, the flow possibly reattaches earlier than first pressure tapping point, due to smaller area for the flow to expand. The static pressure in the duct is nearly equal to free-stream pressure, at low subsonic Mach numbers. There is very minimal impact on the suction occurring at the base region. In the case of correctly expanded sonic and under-expanded sonic flow, the pressure is seen to rise very mildly above the atmospheric pressure and the suction at the base is set to decrease at that point. Post the reattachment point (R.A.P.), the pressure is gradually seen to stabilize and become equivalent to the atmospheric pressure earlier than the exit or at the exit of the pipe, causing an increased suction at the base region. Area ratio determines the size of recirculation zone and that determines the suction levels at the base. The suction occurring at the base becomes stronger as NPR increases, attributing to breaking down of larger vortices into smaller vortices.